If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2ax + bx)(2ax + bx) = 0 Multiply (2ax + bx) * (2ax + bx) (2ax * (2ax + bx) + bx(2ax + bx)) = 0 ((2ax * 2ax + bx * 2ax) + bx(2ax + bx)) = 0 Reorder the terms: ((2abx2 + 4a2x2) + bx(2ax + bx)) = 0 ((2abx2 + 4a2x2) + bx(2ax + bx)) = 0 (2abx2 + 4a2x2 + (2ax * bx + bx * bx)) = 0 (2abx2 + 4a2x2 + (2abx2 + b2x2)) = 0 Reorder the terms: (2abx2 + 2abx2 + 4a2x2 + b2x2) = 0 Combine like terms: 2abx2 + 2abx2 = 4abx2 (4abx2 + 4a2x2 + b2x2) = 0 Solving 4abx2 + 4a2x2 + b2x2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), 'x2'. x2(4ab + 4a2 + b2) = 0 Factor a trinomial. x2((2a + b)(2a + b)) = 0Subproblem 1
Set the factor 'x2' equal to zero and attempt to solve: Simplifying x2 = 0 Solving x2 = 0 Move all terms containing a to the left, all other terms to the right. Add '-1x2' to each side of the equation. x2 + -1x2 = 0 + -1x2 Remove the zero: 0 = -1x2 Simplifying 0 = -1x2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(2a + b)' equal to zero and attempt to solve: Simplifying 2a + b = 0 Solving 2a + b = 0 Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. 2a + b + -1b = 0 + -1b Combine like terms: b + -1b = 0 2a + 0 = 0 + -1b 2a = 0 + -1b Remove the zero: 2a = -1b Divide each side by '2'. a = -0.5b Simplifying a = -0.5bSubproblem 3
Set the factor '(2a + b)' equal to zero and attempt to solve: Simplifying 2a + b = 0 Solving 2a + b = 0 Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. 2a + b + -1b = 0 + -1b Combine like terms: b + -1b = 0 2a + 0 = 0 + -1b 2a = 0 + -1b Remove the zero: 2a = -1b Divide each side by '2'. a = -0.5b Simplifying a = -0.5bSolution
a = {-0.5b, -0.5b}
| R-3.5=-2.1 | | 15=5+y | | 32x^3+13x^3+23x^4= | | 32x^3+13x^3+13x^3= | | 8x-9=3x+-16 | | 6[x+4]=36 | | 6(-17-3y)+2y=10 | | (x+2y)2= | | mx^2+(m-1)x-3=0 | | 130+2x+10=180 | | 4b+7=1b+15 | | 13/19+6y=9 | | 3x^2-27x-30=0 | | 2(x+2)=2x | | 51x^5+119x^9+221x^10= | | 12a+11b+2c+4c-5b-2a= | | -10+7y+6y=9 | | 0.05x-0.6=52 | | 20p+15q+p-4p-5p= | | 3x-3=4y-4 | | 5x-20=6x-40 | | 0.5x+y=-2 | | z^2-(5+2i)z+21+i=0 | | 3x-3=4y-y | | 2+10y-15=3 | | 0.13y+0.09(y+7000)=1510 | | y=0.5+9 | | 12m+2n-6m+9n= | | z^2-(5+2i)+z+21+i=0 | | -13x+7y=-21 | | g(x)=x^2+6x-16 | | 12x-88=4(-2x-7) |